Implementasi Kinerja Aparatur Pemerintah Desa (Menurut UU. Nomor 6 Tahun 2014) - Fresal Arthur Sopamena (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2020)
The village government in carrying out the role should be in accordance with the implementation of the duties of the village government as mandated in Law No. 6 of 2014, but in reality the village government failed to implement it to the community. The results of the research as obtained from the author, and strengthened by observational data, interviews and research conducted, show that the Ridool Village Government in carrying out its activities is not fully in line with the hopes and desires of the Ridool Village community. This is based on the implementation of various village government activities that are not well socialized to the community, even accountability of government activities that are not delivered to the community at all, so that the welfare of the village community served is not in accordance with the demands of carrying out governmental tasks mandated in the Law on Villages.